A Review on the Planning Problem for the Installation of Offshore Wind Farms. Issue 13 (2019) - Rippel, Daniel; Jathe, Nicolas; Becker, Matthias; Lütjen, Michael; Szczerbicka, Helena; Freitag, Michael
Abstract: Offshore wind farms provide a promising technology to produce renewable and sustainable energy. Nevertheless, the installation and operation of offshore wind farms pose a particular challenge to the planning and execution of operations. This article aims to identify requirements towards a decision support tool for the installation planning. Therefore, it provides a review of existing research in planning approaches and summarizes the overall planning problem. Afterwards this problem is decomposed into single tasks, according to their planning horizons. This decomposition shows a high level of interconnection between tasks across all levels. Higher levels provide constraints for the tasks on lower levels, while the results of these tasks are incorporated at higher levels. Finally, the article discusses the advantages and disadvantages of different approaches to solve these tasks.